Effective communication and participative decision-making in selected organisations in Ibadan metropolis (2015)
This study examined the role effective communication and participative decision-making play in organization management, the extent to which employees at the lower cadre of Nigerian organizations are allowed to take part in organizational decision-making and the perception of senior or executive managers of participative decision-making. Data were generated by means of questionnaire and in-depth interview. A total of 207 junior and senior employees of participating organizations filled copies of the questionnaire and five executive managers were interviewed. The data generated from the questionnaire were analyzed using simple percentage statistical method. Responses from the interview were carefully coded and issues of interest were extracted to support the findings of the study. The results of the study revealed that participative decision-making system increases employees' commitment to organizational goals, gives them job satisfaction and motivation, increases organizations' productivity but employees at the lower cadre of Nigerian organizations are not allowed to take part in decisions that affect the strategic goals of the organization even though senior managers have a positive perception of participative decision-making and they see it as important for managing present-day organizations. Further findings revealed that the major channels of communication used to promote participative decision-making and employee-management interrelationship are departmental meetings, suggestion boxes, committee meetings, internal memoranda, official letters and group or team discussions. The implication of this study is that Nigerian organizations need to put in place an environment that allows employees to participate in organization-wide decision-making process.